Iklan Hotel Berbahasa Jepang: Kajian Semantik - Grahayani Karang, Ni Putu (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2016)
One media that is used to attract them is the advertisement media. There are so many Japanese language hotel advertisement that there are some verbal and non verbal elements that are not related, thus it makes these Japanese language hotel advertisement are interesting to be researched. There are three problems that are analysed in this research, they are: first, what is the structure of the Japanese language Hotel advertisement in the printed media?; second, how is the using of the iconic, indexial and simbolic signs in the japanese language hotel advertisement?; and third how are the perception of the Japanese Tourists on the japanese language hotel advertisement which are in the tourism printed media? Those problems are analyzed using van Dijk's (1997) discourse structure theory and semantic theory by Charles Sanders Pierce (1993). This analysis is also supported by the advertisement structure theory by Leech (1966). The analysis result shows that japanese language hotel advertisement has five patterns of advertisement maker structures. On the gramatical element is always optimized the using of particles. The iconic, indexial and simbolic signs which are seen through the advertisement structure make a meaning which is communicated freely. The perception gotten from the tourists is that they tend to enjoy advertisement with complete structure which shows the excellences of that hotel.
Keywords: advertisement, sign, perception